Mapping soil erosion hotspots and assessing the potential impacts of land management practices in the highlands of Ethiopia - Tamene, Lulseged D.; Adimassu, Zenebe; Ellison, James; Yaekob, Tesfaye; Woldearegay, Kifle; Mekonnen, Kindu; Thorne, Peter J.; Le, Quang Bao (Elsevier, 2017)
An enormous effort is underway in Ethiopia to address soil erosion and restore overall land productivity. Modelling and participatory approaches can be used to delineate erosion hotspots, plan site- and context-specific interventions and assess their impacts. In this study, we employed a modelling interface developed based on the Revised Universal Soil Loss Equation adjusted by the sediment delivery ratio to map the spatial distribution of net soil loss and identify priority areas of intervention. Using the modelling interface, we also simulated the potential impacts of different soil and water conservation measures in reducing net soil loss. Model predictions showed that net soil loss in the study area ranges between 0.4 and 88 t ha− 1 yr− 1 with an average of 12 t ha− 1 yr− 1. The dominant soil erosion hotspots were associated with steep slopes, gullies, communal grazing and cultivated areas. The average soil loss observed in this study is higher than the tolerable soil loss rate estimated for the highland of Ethiopia. The scenario analysis results showed that targeting hotspot areas where soil loss exceeds 10 t ha− 1 yr− 1 could reduce net soil loss to the tolerable limit (< 2 t ha− 1 yr− 1). The spatial distribution of soil loss and the sediment yield reduction potential of different options provided essential information to guide prioritization and targeting. In addition, the results can help promoting awareness within the local community of the severity of the soil erosion problem and the potential of management interventions. Future work should include cost-benefit and tradeoff analyses of the various management options for achieving a given level of erosion reduction.